Observation of the interactions of silver nanoparticles (AgNPs) mediated by acid in the aquatic matrices using in-situ liquid cell transmission electron microscopy - Fernando, Ishara (2021)
The properties of the solution matrix play a prominent role in determining the interactions between the silver nanoparticles (AgNPs) when they are present in the aquatic environment. Here, using in situ liquid cell transmission electron microscopy (LCTEM), we show that the interaction of AgNPs is predominantly affected by the solution pH. Reducing the pH in the solution will accelerate the aggregation of AgNPs due to the alteration of the charge cloud around the NPs. Aggregates formed in this scenario were non spherical and irregular shaped and were stable under the electron beam irradiation. Individual AgNPs and smaller aggregates moved randomly and approached the larger aggregates before the aggregation process came to an end. We found that during the aggregation process, the mode of jump to contact and the pairwise approach of aggregation differed according to the composition of the solution. Observations made using the LCTEM were further explained using empirical formulae. Our observation on the pH induced interactions provides important insights on predicting the behavior of AgNPs released through many anthropogenic activities in the environment.